Caracterização do efeito vasoconstritor do veneno do sapo Rhinella marina em ratos wistar - Santos, Cintia Vieira dos (2022)
Rhinella marina toad is abundant in Brazil. Its poison has a large amount of bufadienolides, which are extensively studied due to its bioactivity. Our hypothesis is that R. marina poison has a NA+ /K+ ATPase-mediated vasoconstrictor action. Thus, our aim was to characterize a vasoactive action of this venom in the aorta of male Wistar rats. First, the poison was collected in a sustainable way from frogs in the municipality of Sinop-MT. Poison was processed and the alcoholic extract obtained was used in the experiments. Vascular reactivity was studied through concentration-curves to R. marina (10 ng/mL to 200 μg/mL) in aortic segments with and without endothelial layer. The possible mechanisms of action involved in vasoconstrictor response were evaluated as well as NA+ /K+ ATPase activity. We performed in vivo tests for the concentrations 0,1 to 0,8 mg/kg to determine cardiovascular alterations after intravascular infusion of this compound. Poison-induced vasoconstriction was observed in the presence and the absence of endothelium. L-NAME incubation confirmed endothelial modulation of the response by NOS pathway. Regarding to the mechanisms of action, it was observed decreased contractility induced by incubation with indomethacin (COX inhibitor), nifedipine (L-type calcium channels blocker), BQ-123 (ETA receptors antagonist) and ketanserin (5-HT2 receptors antagonist), indicating active participation of this pathways on contractile response. Apocynin (NADPH oxidase inhibitor) did not altered contractility. Incubation with prazosin (α1- adrenergic receptors antagonist) notably decreased contractile response both in power and effectiveness, suggesting that the R. marina-induced contraction is dependent of adrenergic pathway. In the NA+ /K+ ATPase pump test, the poison potentiated that enzyme hyperpolarizing response since this group presented higher relaxing percentage comparing to control group. When administrating this extract intravascularly in vivo, it was observed increase in blood pressure and decrease in heart rate. The results were immediate and transitory, highlighted during poison infusion and in its higher concentrations. Thus, the poison of Rhinella marina toad has an important vasoconstrictor action and the knowledge of its pharmacodynamics may lead to the development of new treatments with cardiovascular focus.